ETHNIC CONFLICTS IN NIGERIA: A STUDY OF TIV JUKUNSOCIO ECONOMIC PERSPECTIVE - Joshua, Ruth Yohanna (Journal of Techno-Social, 2016)
Tiv-Jukun conflict has a long history of occurrence and reoccurrence over a period of time. In many instances, the conflicts have resulted in the destruction of lives and properties and internal displacement of civilians. The conflict has affected the relationship between the two ethnic groups who have been living together cordially. Previous studies on the conflict have not given proper attention to the socio-economic perspective on the conflict. This paper presents the root and remote causes of the Tiv Jukun conflict. Identifying the triggers and drivers of conflict between the two ethnic groups could help in bringing about a lasting solution to the crisis. Interviews were used to illicit the opinion of various demographics of both ethnic groups. Findings indicate among others competition over land resources and the desire for each ethnic group to attain political position for the benefit of its ethnic group in terms of socio-economic amenities such as education, healthcare services and employment. In order to promote a peaceful co-existence, the Nigerian government should implement the report of the previous committees, a proper sharing formula between the two ethnic groups and address the issue of citizenship rights constitutionally.